2011
DOI: 10.1364/oe.19.015792
|View full text |Cite
|
Sign up to set email alerts
|

Antireflective silicon surface with vertical-aligned silicon nanowires realized by simple wet chemical etching processes

Abstract: Silicon antireflection is realized with vertical-aligned SiNWs by using improved metal-induced etching technique. The spectral responses of the transmission, reflection, and absorption characteristics for the SiNWs of different lengths are investigated. In order to realize short SiNWs to provide sufficiently low reflection, a post chemical etching process is developed to make the nanowires have a larger length fluctuation and/or tapered structure. The use of short SiNWs can allow a faster process time and avoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 15 publications
3
25
0
Order By: Relevance
“…Silicon nano structures with high aspect ratio have recently attracted extensive attention due to their excellent optical properties . For photoelectric devices such as photovoltaic devices and photoresistors, enhancements in the incident photon absorption by the semiconductor materials with nanostructure can improve the photoelectric energy conversion efficiency and device sensitivity .…”
Section: Introductionmentioning
confidence: 99%
“…Silicon nano structures with high aspect ratio have recently attracted extensive attention due to their excellent optical properties . For photoelectric devices such as photovoltaic devices and photoresistors, enhancements in the incident photon absorption by the semiconductor materials with nanostructure can improve the photoelectric energy conversion efficiency and device sensitivity .…”
Section: Introductionmentioning
confidence: 99%
“…Different methods of making graded-index AR coatings have been reported, including lithography and wet etching [3], sol-gel process [4], integrated nanoisland coating arrays on nano-conical-frustum arrays [5], improved metal-induced chemical etching [6], and oblique-angle deposition [7,8]. At present, the lowest refractive index n 1.05 was reported by Xi and Schubert et al [7] using oblique-angle deposition, and their study showed that oblique-angle deposition has good control over the refractive index profile when the substrates are flat.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, an effective antirefl ection coating (ARC) for a higher optical transmittance can contribute to the accomplishment of improved contrast and brightness in display devices and higher levels of energy conversion effi ciency in solar panels. [2][3][4][5][6] Various methods, such as lithography, obliqueangle deposition, catalytic etching, chemical vapor deposition, and a sol-gel process, have been reported. An ideal ARC should satisfy the requirements of a quarter-wavelength fi lm thickness and a fi lm η of ( η s ) 0.5 , where η s denotes the η of the substrate.…”
mentioning
confidence: 99%
“…Traditional ARCs improve optical transmittance by introducing destructive interference between refl ected light beams from the air-fi lm and fi lm-substrate interfaces. [2][3][4][5] However, these methods may lack cost-effectiveness and high-throughput capabilities due to the requirements of vacuum processing, multiple etching steps, or because of the limited controllability of η .Recently, highly porous block copolymer (BCP) thin fi lms were applied to the fabrication of ARC due to the excellent low-cost solution processability and facile tunability of η when controlling the fraction of the pores generated by the selective removal of one block. [ 1 ] However, an ARC with a homogeneous η can achieve high transmittance only in narrow wavelength and incidence angle ranges, which are fi xed by its thickness and refractive index.…”
mentioning
confidence: 99%
See 1 more Smart Citation